Students' Collaboration Skills through Project-Based Learning Model Using Digital Poster on Virus Reproduction Concepts - Fatonatullaillah, Indah; Nugroho, Nur Azizah Haffaf; Dewi, Siska Agustin; Hendriyani, Mila Ermila; Rubino, Rubino; Camara, Jun S.; Polyiem, Titiworada (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to improve students' collaboration skills on virus reproduction material by using digital posters to apply the Project Based Learning (PjBL) model. Qualitative methods were used to analyze data collected through observation, interviews, and documentation in class X of one of the public high schools in Serang City, Banten. Students were tasked to create a digital poster due to group work, where they collaborated to identify the stages of the lytic and lysogenic cycles in viral reproduction. The results showed that the PjBL model improved students' collaboration skills, including communication skills, responsibility, and mutual respect for opinions. Most students have shown good collaboration skills, although some are still passive in the discussion. Teachers and students also faced obstacles, such as a lack of commitment from some group members. Thus, implementing PjBL using digital poster media effectively builds collaboration skills, although further support is needed to ensure that all group members are actively involved. This research suggests using innovative media and methods to optimize collaborative learning in the classroom.